A delay and energy aware coordination mechanism for WSAN. (24th February 2016) - Kakarla, Jagadeesh; Majhi, Banshidhar; Battula, Ramesh
Summary: In this paper, a delay and energy aware coordination mechanism (DEACM) has been devised for wireless sensor–actor networks. In DEACM, a two‐level hierarchical K‐hop clustering mechanism is used to organize the sensors and actors for communication. In the first level, sensors form a K‐hop cluster using actors as cluster heads, and sink is made as the cluster head in the second level to form a cluster among actors. Sensor nodes, which are 1‐hop away from the actors, also called as relay nodes are elected as backup cluster head (BCH) based on the residual energy and node degree. BCH collects the data from sensors when an actor is away to perform actions in the affected area. The scheme is evaluated through exhaustive simulation in NS2 along with other existing schemes. Different parameters like average event waiting time, event reliability, and average energy dissipation are compared, varying the number of sensors, actors, and data transfer rate. In general, it is observed that the proposed DEACM outperforms other existing schemes. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A two‐level hierarchical K‐hop clustering mechanism is used to organize the sensors and actors for communication. Sensor nodes, which are 1‐hop away from the actors, also called as relay nodes, are elected as backup cluster head based on the residual energy and node degree. The priority‐based event reporting mechanism tries to deliver the maximum number of packets to the actor within the bounded delay.